Weakened Atlantic Meridional Overturning Circulation Contributes to Opposite Responses of ENSO and the Atlantic Niño/Niña to Greenhouse Warming - Yun Yang; Lixin Wu; Wenju Cai; Xi Cheng; Xinyue Mei; Fan Jia; Shujun Li; Tao Geng; Yuhu Chen; Hong Wang (Geophysical Research Letters)
Abstract The Pacific El Niño‐Southern Oscillation and the Atlantic Niño/Niña change oppositely in the 21st century. Here, we find the weakened Atlantic Meridional Overturning Circulation (AMOC) plays a key role. Via reducing the equatorial Pacific trades and the Atlantic poleward heat transport, the weakened AMOC contributes to, at surface, a similar Niño‐like sea surface temperature (SST) warming and a strengthened atmospheric stratification in both basins, while, at subsurface, a western Pacific cooling in comparison to an intense Atlantic warming. The distinct subsurface changes induce strengthened Pacific oceanic stratification to enhance Bjerknes feedback, in contrast to an insignificant change in the Atlantic. Moreover, the similar surface changes exert different impacts, with a strengthened atmospheric stratification suppressing the Atlantic Bjerknes feedback, an influence offset in the Pacific by an eastward shift of deep convection due to Niño‐like SST warming. Such offset is absent in the Atlantic owing to the northern‐hemisphere‐located deep convection.